Take a Number? Surgical Waiting Times for Transurethral Bladder and Prostate Surgery in Albany, New York. Issue 5 (September 2015) - Walker, Adam; Gin, Greg; Feustel, Paul; Kogan, Barry
Abstract : Introduction: : Surgical waiting times are considered an important measure of quality of health care delivery. We determined the surgical waiting times for transurethral bladder tumor resection and transurethral prostate resection at our institution, and examined the factors that affected these waiting times. Methods: : We performed a retrospective chart review of 272 consecutive patients who underwent transurethral bladder tumor resection and 113 consecutive patients who underwent transurethral prostate resection. We determined dates of referral, initial evaluation, decision for surgery and date of surgery. We also examined patient factors such as age, gender, indication for surgery, specific surgeon, type of insurance, new vs established patient, ASA® score and final tissue pathology. Results: : Median time from the decision for surgery to the date of surgery was 22 days for patients undergoing transurethral bladder tumor resection. Factors associated with a shorter waiting time were year of surgery and specific surgeon. Median waiting time for patients undergoing transurethral prostate resection from decision for surgery to date of surgery was 27 days. Factors associated with a shorter waiting time included age, Medicare insurance coverage, ASA score greater than 2 and indication for surgery. Conclusions: : These are the first data to our knowledge from the U.S. health care system in examining wait times for transurethral bladder cancer surgery and transurethral prostate surgery. With the increasing focus on improving quality of care, surgical waiting times may be used in the U.S. as a quantifiable measure of quality in health care systems. The factors associated with longer waiting times in this study may allow health care systems to target areas for improvement.